Human cytomegalovirus neutralising antibodies and increased risk of coronary artery disease in Indian population - Mundkur Lakshmi Ashutosh; Shivanandan Hemapriys; Hebbagudi Sridhara; Endrész Valéria; Varma Meenakshi; Rao Veena; Gönczöl Éva; Kakkar Vijay Vir (British Medical Journal Group, 2012)
Background Several studies have reported a conflicting association between cytomegalovirus (CMV) infection and coronary artery disease (CAD) based on the levels of total anti-CMV antibodies. However, none have estimated the levels of specific neutralising antibodies (NA) to CMV, which may be clinically more relevant. Objective To determine whether CMV-NA titres show a better association with CAD compared with total anti-CMV antibody levels. Design CMV-NA titres were measured by micro-neutralisation assay and anti-CMV IgG antibodies using ELISA in 391 consecutive CAD patients compared with the same number of controls (N = 782), and 91 patients reporting recurrent cardiac events during a 4-year follow-up compared with those without a recurrent event (N = 182). Levels of inflammatory markers, interleukin 6, high-sensitivity C reactive protein, fibrinogen and secretory phospholipase A2 (sPLA2), were measured by ELISA. Analysis of variance and logistic regression were used for statistical analyses. Results High CMV-NA titres showed a positive association with CAD occurrence (OR 2.24, 95% CI 1.31 to 3.85, p = 0.003) and recurrent cardiac events in CAD patients (OR 4.65, 95% CI 1.21 to 17.86, p = 0.025) compared with total CMV antibodies (OR 1.67, 95% CI 1.04 to 2.69, p = 0.034, and 2.70, 1.04 to 7.02, p = 0.040, respectively). Patients with higher quartile of CMV-NA titres and sPLA2 levels had an adjusted OR of 7.82 (95% CI 1.87 to 32.65, 0.005) for recurrent cardiac events compared with those with the lowest quartiles for both markers. Conclusion These findings suggest that high CMV-NA titres in combination with inflammatory markers improve prediction of cardiac events in the Asian Indian population.